The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1002/aic.10358
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐based design and experimental evaluation of a spatially controllable CVD reactor

Abstract: Most conventional chemical vapor deposition (CVD) systems do not have the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…While it is non-trivial to generate large composition variation in a CVD chamber, they can be achieved by controlling the flow of precursor gases. 60,61 Equally important to achieving compositional variations on the wafers is the need to achieve process parameter (i.e., pressure and flow) variations.…”
Section: Advanced Gate Stack Materialsmentioning
confidence: 99%
“…While it is non-trivial to generate large composition variation in a CVD chamber, they can be achieved by controlling the flow of precursor gases. 60,61 Equally important to achieving compositional variations on the wafers is the need to achieve process parameter (i.e., pressure and flow) variations.…”
Section: Advanced Gate Stack Materialsmentioning
confidence: 99%
“…In the case of CVD, we achieve this through a reactor design, 19 which employs a segmented gas injection showerhead with exhaust gas recirculation ͑Fig. 21 The present three-segment design of the CVD showerhead is intended to prove feasibility, validate models, and demonstrate control. With this design, we can produce desired gradients of gas impingement or deposition-or uniformity-across the wafer surface.…”
Section: Spatially Programmable Cvd "Sp-cvd…mentioning
confidence: 99%
“…21 Also, ͑2͒ high gas feeding rates will prevent gas diffusion ͑both ISM-wafer and ISM-BD͒ from other segments.…”
Section: A Mechanisms Of Intersegment Gas Diffusionmentioning
confidence: 99%
“…In the second example we consider data produced by the Programmable CVD reactor system [5,6,9,10], a reactor designed to test spatially controlled CVD concepts. The main feature of this system is its segmented showerhead design that allows independent control of feed gas composition to each segment.…”
Section: Model Comparison For the Spatially Programable Cvd Reactormentioning
confidence: 99%
“…In Taylor and Semancik [12], microhotplate devices were used to control the temperature in an array of micro-scale substrate samples; it was found that temperature gradients in the microhotplate supports resulted in a microstructurally graded film on the support legs. Finally, the Programmable Reactor system [5,6,9,10] features a segmented shower head design where each segment is fed individually with reactant gases and exhaust gas is pumped back up through each segment. This concept was tested in a three-zone prototype tungsten deposition system to evaluate the system's ability to manipulate gas phase composition across the wafer surface [5,6] and to demonstrate its true programmable nature using a modelbased approach to controlling spatial deposition patterns across the wafer surface [9,10].…”
Section: Combinatorial Cvdmentioning
confidence: 99%